Mental health in athletes: Where are the treatment studies? - Ekelund, R.; Holmström, S.; Stenling, A. (Frontiers in Psychology, 2022)
In recent years, athletes` mental health has gained interest among researchers, sport practitioners, and the media. However, the field of sport psychology lacks empirical evidence on the effectiveness of psychotherapeutic interventions for mental health problems and disorders in athletes. Thus far, intervention research in sport psychology has mainly focused on performance enhancement using between-subject designs and healthy athlete samples. In the current paper, we highlight three interrelated key issues in relation to treating mental health problems and disorders in athletes. (i) How are mental health and mental health problems and disorders defined in the sport psychology literature? (ii) How are prevalence rates of mental health problems and disorders in athletes determined? (iii) What is known about psychotherapeutic interventions for mental health problems and disorders in athletes? We conclude that the reliance on different definitions and assessments of mental health problems and disorders contributes to heterogeneous prevalence rates. In turn, this limits our understanding of the extent of mental health problems and disorders in athletes. Furthermore, knowledge of the effectiveness of psychotherapeutic interventions for athletes with mental health problems and disorders is scarce. Future research should include athletes with established mental health problems and disorders in intervention studies. We also propose an increased use of N-of-1 trials to enhance the knowledge of effective psychotherapeutic interventions in this population.